1971
DOI: 10.1104/pp.47.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin Activity in Water-stressed Shoots

Abstract: Water stress applied to the plant shoot or Dowex 50W x 4 50-100 mesh). The column was rinsed with 1 liter of 70%to (v/v) ethanol and with H20. The active substance was eluted with 1 liter of 4 N NH40H. The eluate was concentrated to 300 ml under vacuum at 45 C, and the pH was adjusted to 8.0 and extracted twice on a shaker for 20 hr with 200 ml of n-butanol. The extracts were then combined and dried under vacuum. The residue was dissolved in 5 ml of water at pH 8. This solution was divided into equal portion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
1

Year Published

1975
1975
1990
1990

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(43 citation statements)
references
References 14 publications
2
39
0
1
Order By: Relevance
“…These observations are in contrast to an earlier report (25) tion was eliminated. In light of these observations and previous studies of Itai and Vaadia (14,15) and Ben-Zioni et al (8) which provided evidence that exogenously applied cytokinin was capable of relieving the effects of small water deficits, it was thought that cytokinin treatment should relieve the effects of small water deficits on the greening process; namely, reduce or eliminate the lag phase in Chl accumulation. However, cytokinin was neither effective in reducing the 3-to 4-hr lag in Chl accumulation nor in eliminating the delay in lowering of the leaf Chl a/b ratio (Figs.…”
Section: Resultsmentioning
confidence: 93%
“…These observations are in contrast to an earlier report (25) tion was eliminated. In light of these observations and previous studies of Itai and Vaadia (14,15) and Ben-Zioni et al (8) which provided evidence that exogenously applied cytokinin was capable of relieving the effects of small water deficits, it was thought that cytokinin treatment should relieve the effects of small water deficits on the greening process; namely, reduce or eliminate the lag phase in Chl accumulation. However, cytokinin was neither effective in reducing the 3-to 4-hr lag in Chl accumulation nor in eliminating the delay in lowering of the leaf Chl a/b ratio (Figs.…”
Section: Resultsmentioning
confidence: 93%
“…Itai and Vaadia (18), who first reported on decreased cytokinin activity after water stress and its increase following recovery, suggested that these changes resulted from inactivation of the hormone and subsequent reversal of this inactivation. Our data support these findings without having any bearing on the detailed mechanism involved in the modifications in cytokinin activity induced by water stress.…”
Section: Resultsmentioning
confidence: 99%
“…In leaves, water stress causes a rapid increase in ABA content (15, 31) and a sharp decrease in cytokinin activity (18). ABA is known to induce stomatal closure with resulting decreased transpiration in many types of leaves (9,16,19,23,27,28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these plant responses are the direct result of physical changes accompanying loss of cell turgor (6) while other responses could be due to altered levels of plant growth regulators. Plants exposed to water-limited conditions have been shown to have elevated levels of ABA (25) and ethylene (2) and reduced amounts of cytokinin (16) and gibberellin (1).…”
mentioning
confidence: 99%